Irak’ta “muktedir” ve “müşteki” bir ittihatçı: süleyman nazif bey’in basra valiliği - (:unkn) unknown (My University, 2012)
II. Meşrutiyet döneminde Irak kıtasının üç vilayetinde de valilik görevinde bulunmuş olan Süleyman Nazif Bey’in Basra valiliği birçok açılardan önem arz etmektedir. Bu dönem İttihat ve Terakki Cemiyeti’nin Arap vilayetlerine yönelik politikasını tahlili için bir örneklem teşkil ettiği gibi, aynı zamanda Cemiyet’in buraya atamış olduğu vali tipolojisine de güzel bir örnek oluşturmaktadır. Basra valiliği döneminde izlediği sosyo-ekonomik, siyasal ve bayındırlık politikalarıyla son derece “muktedir” bir vali imajı çizen Süleyman Nazif, aynı zamanda gerek eşrafla gerekse yerel memurlarla girdiği polemikler itibariyle Babıali’ye sürekli şikayet arz eden bir tablo çizmiştir. Bununla birlikte, Süleyman Nazif Bey’in II. Meşrutiyet döneminde Basra vilayetinde görev yapan valiler içerisinden en etkililerinden biri olduğunu söylemek yanlış olmayacaktır.

The governorship of Suleyman Nazif Bey, who has been worked as a governor in both three vilayats of Iraq during the second constitutional period, is of great importance in many aspects. As an illustration to analyze the Committee of Union and Progress`s policy towards Arab periphery, this period also forms a good example for the typology of governors appointed by the CUP governments. Suleyman Nazif built an image of a capable governor by his policy towards socio- economic, political problems and public works of Basra. Nevertheless he has sent so many petitions to Sublime Porte as a consequence of his polemics both with the notables and local officials. However it is worth saying that; Suleyman Nazif Bey was one of the most efficient among the governors ruled in Basra province during the second constitutional period.
a powerful and complainant supporter of cup (committee of union and progress) in ıraq: the basra governorship of suleyman nazif bey